'WHY SOMETIMES I'VE BELIEVED AS MANY AS SIX IMPOSSIBLE THINGS BEFORE BREAKFAST': TRANSLATING CLINICAL EXPERIENCE INTO INJURY PREVENTION OUTCOMES. (7th October 2012) - Barker, R
Abstract : Background: Clinicians in a variety of fields are at the receiving end of many injury incidents. Information relevant to preventing injury is often discussed, less often documented, and rarely acted upon other than after-the-fact behavioural advice to the patient or caregiver. The latter is due to many factors, including work load, lack of non-clinical time, lack of awareness of relevant injury prevention networks and a limited understanding of the complex frameworks that underpin community safety and injury prevention. Aims/Objectives/Purpose: To describe how non-clinical injury prevention practitioners and clinical health practitioners can engage to develop stronger and more effective injury prevention partnerships. Methods: The author works as an emergency paediatrician and directs the Queensland Injury Surveillance Unit. In collaboration with a range of partners from diverse backgrounds, she has been able to deliver several injury prevention outcomes, across a variety of injury topics. The author also has experience in attempting to engage clinicians (nursing and medical) to participate in injury prevention activities. Results/Outcome: The presentation will describe ways of collaborating across silos using recent injury prevention activities to illustrate how outcomes can be achieved. This will be presented under the following headings:  Clinicians don't answer emails: collating clinical cases of lye water ingestion in Australia  But the right answer is obvious: toddler falls from balconies and a quest to change the Australian Building code  True injury surveillance: engaging families and clinicians in reporting product related injury Significance/Contribution to the Field: This paper is a call for greater collaborative engagement between injury prevention practitioners and clinicians, in order to more effectively deliver injury prevention outcomes.